2013
DOI: 10.1103/physrevc.88.064305
|View full text |Cite
|
Sign up to set email alerts
|

Ground-state phase transition in odd-Aand odd-odd nuclei nearN=90

Abstract: Ground-state phase transitions in odd nuclei are examined. Especially, the phase transitions in odd-odd nuclei are revealed. It is found that odd-even effects may reach their maximal or minimal values around the critical point at N = 90; the signals of phase transition in odd nuclei are greatly enhanced relative to those in the adjacent even-even species. Moreover, a pairing model analysis of the phase transition in Sm isotopes indicates that the critical behaviors related to pairing may be driven by the decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 53 publications
1
24
0
Order By: Relevance
“…The odd-even differences of α-decay energy D(Q α ) and double β − -decay energy D(Q 2β − ) in Sm and Eu isotopic chains were investigated previously [25], and the results suggested show that D(Q α ) and D(Q 2β − ) all reach their maximal values around N ≈ 90 based on experimental data but without theoretical model calculations. The odd-even differences of α-decay energy D(Q α ) and double β − -decay energy D(Q 2β − ) for Sm, Gd, and Nd are also calculated in the present model according to (16) and (17).…”
Section: Odd-even Differences Of α-Decay and Double β − -Decay Energymentioning
confidence: 99%
See 4 more Smart Citations
“…The odd-even differences of α-decay energy D(Q α ) and double β − -decay energy D(Q 2β − ) in Sm and Eu isotopic chains were investigated previously [25], and the results suggested show that D(Q α ) and D(Q 2β − ) all reach their maximal values around N ≈ 90 based on experimental data but without theoretical model calculations. The odd-even differences of α-decay energy D(Q α ) and double β − -decay energy D(Q 2β − ) for Sm, Gd, and Nd are also calculated in the present model according to (16) and (17).…”
Section: Odd-even Differences Of α-Decay and Double β − -Decay Energymentioning
confidence: 99%
“…Furthermore, these quantities only depend on the number of nucleons with abundant experimental data available [2,[4][5][6]. However, through the analysis of these quantities and their odd-even differences [25], it is observed that nearly all the odd-even differences reach their extreme values (maximum or minimum) around the critical point, which, therefore, are more sensitive and suitable to be used as effective order parameters to manifest the shape phase transition. Hence, in the following, besides the odd-even mass differences P(Z, N), the odd-even differences of two-neutron separation energy, α-decay energy and double β − -decay energy will be calculated, where the odd-even difference of the two-neutron separation energy is given by…”
Section: The Nilsson Mean-field Plus Standard Pairing Model and Imentioning
confidence: 99%
See 3 more Smart Citations